Singapore Management University Report to Stakeholders 2015 - 2016 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2016)
As we enter the third year of our journey towards SMU Vision 2025, we need to build on the momentum that has been generated by the dedication and spirit of collaboration that has developed in the SMU community. SMU continues to transform the future of education with ground-breaking innovations in our undergraduate curriculum. At the same time, our postgraduate, professional and executive development offerings continue to expand in number and receive greater global recognition and prestigious accolades.